SENYAWA ANTIBAKTERI GOLONGAN FLAVONOID DARI BUAH BELIMBING MANIS (Averrhoa carambola Linn.L) - I M. Sukadana (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
Isolation and identification of active antibacterial compounds from star fruit (Averrhoa carambola Linn). hasbeen carried out. As much as 140.56 g of concentrated methanol extract was resulted from 10 kg star fruit that wasmacerated using methanol. This extract was dissolved into methanol-water (7:3) and then partitioned with n-hexaneand chloroform respectively, resulting in concentrated extracts of 0.10 g of n-hexane, 0.07 g of chloroform, and48.01 g of water. The result of phytochemical test for flavonoid for all of the extracts suggested that water extractsshowed most be test intense to the flavonoid.Separation of water extract using column chromatography resulted in FB fractions that was orange as muchas 0.2027 g and contains flavonoid. Infra red and UV-vis spectroscopy were employed in order to identify the FBfraction. The result of identification showed that isolate (fraction FB) was cathechin compounds which containedhydroxyl groups at C-3, C-7 and C-4’. It also had functional groups like –OH, C-H aromatic, C-H aliphatic, C=Caromatic, C-O alcohol, and it did not contained C=O carbonyl group. The isolate inhibited E.coli growth at 100 ppmand S. aureus grouth at 500 ppm.